2005
DOI: 10.1523/jneurosci.4847-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of Canary HVC Neurons for the Bird's Own Song: Modulation by Photoperiodic Conditions

Abstract: To what extent seasonal factors modify the neuronal functional properties within the nuclei of the avian song system remains an open question. In adult songbirds, neurons of the song premotor nucleus HVC (used as a proper name) exhibit selective responses for the bird's own song (BOS). Here we examine whether, outside the breeding season, when songs are less stereotyped, HVC neurons of male canaries still respond selectively to the BOS produced during this period. In an initial experiment, single-unit recordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 65 publications
(99 reference statements)
4
29
1
Order By: Relevance
“…These findings resonate with studies in canaries, in which the HVC selectivity for the bird's own vocalizations were enhanced during the long-day (breeding) season relative to short-days [78]. Though not explicitly measured in that study, their finding suggests a role for seasonal changes in plasma- or brain-derived steroids such as estrogens in modulating HVC neuronal selectivity in a more protracted, seasonal timescale.…”
Section: Estrogens Can Rapidly Influence Sensorimotor Integrationsupporting
confidence: 84%
“…These findings resonate with studies in canaries, in which the HVC selectivity for the bird's own vocalizations were enhanced during the long-day (breeding) season relative to short-days [78]. Though not explicitly measured in that study, their finding suggests a role for seasonal changes in plasma- or brain-derived steroids such as estrogens in modulating HVC neuronal selectivity in a more protracted, seasonal timescale.…”
Section: Estrogens Can Rapidly Influence Sensorimotor Integrationsupporting
confidence: 84%
“…For example, extracellular single- and multi-unit recordings have shown that in the sensorimotor nucleus HVC of the canary ( Serinus canaria ), long-day photoperiods significantly increase spontaneous activity, increase the proportion of putative interneurons, and enhance neural selectivity (in males) for BOS (Del Negro and Edeline, 2002; Del Negro et al, 2005, 2000). On some level, these results are similar to those reported by Remage-Healey and Joshi (2012) for HVC neurons after manipulation of local E 2 levels in NCM of the non-seasonally breeding zebra finch (see section 3.4.1 above).…”
Section: Estrogens and Auditory Function In Animal Modelsmentioning
confidence: 99%
“…Tian et al, 2001) or for the animal's own vocalization in the high vocal center (HVC) of songbirds (e.g. Lewicki and Konishi, 1995;Margoliash, 1983;Mooney, 2000;Theunissen and Doupe, 1998;Del Negro et al, 2005).…”
Section: For Natural Stimulimentioning
confidence: 99%